A proton/macromolecule-sensing approach distinguishes changes in biological membrane permeability during polymer/lipid-based nucleic acid delivery. Issue 21 (21st May 2021) - Boonstra, Eger; Hatano, Hiroaki; Miyahara, Yuji; Uchida, Satoshi; Goda, Tatsuro; Cabral, Horacio
Abstract : Using a proton-sensing transistor, changes in membrane permeability induced by transfection reagents were assessed, shedding light on endosomal escape mechanisms. Abstract : Endosomal escape is crucial for the delivery of nucleic acids. However, the understanding of the underlying mechanisms is still deficient. In this work, we explored the effects of lipid- and polymer-based transfection reagents on the permeability of cellular membranes through an innovative method combining a proton-sensing transistor and a cytosolic LDH leakage assay, which allows us to distinguish between modes of molecule permeation that may occur during endosomal escape. By testing the commercial reagents lipofectin and in vivo JetPEI under physiological and endosomal pH conditions, we found that both lipid- and polymer-based transfection reagents have pH-dependent pore-forming activity, with the former creating smaller pores than the latter. This versatile approach of assessing carrier–membrane interactions is expected to contribute to the development of next-generation nucleic acid delivery systems.